2014
DOI: 10.1089/apc.2014.0156
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Smartphone Application Incorporating Personalized Health-Related Imagery on Adherence to Antiretroviral Therapy: A Randomized Clinical Trial

Abstract: Poor adherence to combination antiretroviral therapy (ART) is a major global challenge. In this study we examined the efficacy of a smartphone application incorporating personalized health-related visual imagery that provided real-time information about the level of medication and the patient's level of immunoprotection, in order to improve adherence to ART. We randomized 28 people on ART to either a standard or augmented version of the smartphone application. The augmented version contained components that il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
138
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(139 citation statements)
references
References 37 publications
1
138
0
Order By: Relevance
“…A randomized controlled trial (n = 431) of text reminders in adults have been shown to improve adherence to ART, 23 and requires further investigation in adolescents and young adults. Another smaller randomized controlled trial (n = 28) 24 showed improved adherence with a smartphone adherence application, demonstrating the potential for innovative technological approaches in improving medication compliance.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized controlled trial (n = 431) of text reminders in adults have been shown to improve adherence to ART, 23 and requires further investigation in adolescents and young adults. Another smaller randomized controlled trial (n = 28) 24 showed improved adherence with a smartphone adherence application, demonstrating the potential for innovative technological approaches in improving medication compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Advantages associated with the smartphone-enabled survey that was accessible via the Pfizer Meds application included increased accuracy of data entry relative to paper surveys, timely 17 Final PfizerMeds Chantix App Manuscript.doc collection of participant responses, and a relative cost reduction compared to survey administration by a separate stand-alone data source.…”
Section: Principal Resultsmentioning
confidence: 99%
“…Several studies have demonstrated the efficacy of medication and counseling to support smoking cessation. In a large prospective, randomized, double-blind, active-and placebo-controlled pharmacotherapy trial which evaluated the neuropsychiatric safety and efficacy of varenicline, bupropion, and nicotine replacement therapy (NRT) patch, versus placebo, varenicline showed superior efficacy to placebo (p <0.0001) and both bupropion and NRT patch (p <0.0001) at the end of treatment (weeks 9 through 12) and follow-up (weeks [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Bupropion showed similar efficacy to NRT patch (p=0.6002) and both showed superior efficacy versus placebo (p <0.0001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study found that the visual animations promoted more positive beliefs about the illness, and motivated behavioural change including enhanced exercise and quicker return to normal activities. Another computer simulation of HIV virus infection and the protection provided by medication resulted in improved patient adherence to prescribed medication [12].…”
Section: The Virtual Physiological Humanmentioning
confidence: 99%